Reading the Allegorical Intertext : Chaucer, Spenser, Shakespeare, Milton. - Anderson, Judith (Fordham University Press, 2008)
Judith H. Anderson conceives the intertext as a relation between or among texts that encompasses both Kristevan intertextuality and traditional relationships of influence, imitation, allusion, and citation. Like the Internet, the intertext is a state, or place, of potential expressed in ways ranging from deliberate emulation to linguistic free play. Relatedly, the intertext is also a convenient fiction that enables examination of individual agency and sociocultural determinism. Anderson?s intertext is allegorical because Spenser?s Faerie Queene is pivotal to her study and because allegory, und.